(untitled) (International conference on multidisciplinary science, 2025)
This article discusses the importance of the mother tongue in society and the life of the individual, its role in the formation of national identity, and the issues of language development in the context of globalization from a scientific and theoretical perspective. The inextricable link between the mother tongue and the education system, culture, and social consciousness is analyzed, and current directions for its preservation and development are indicated. The conclusions presented substantiate that the mother tongue is an important factor in the stability and spiritual development of society.